First Record of a comunal roost of Short-toed Eagles Circaetus gallicus during migration at the Strait of Gibraltar - Muñoz, Antonio Román; Toxopeus, Bert; Elorriaga, Javier; González, Juan Miguel; Yáñez, Beatriz (My University, 2010)
Communal roosting and its adaptive function for birds have been widely studied. Both juveniles and adults of social bird species normally concentrate in communal roosts, and the protection of these sites may be of conservation importance. The Short-toed Eagle Circaetus gallicus is a migratory, medium-sized tree-nesting raptor whose breeding range in the Western Palaearctic extends from northwest Africa and Iberia through central and southern France, extending northeastward through eastern Poland and the Baltic States and into the Middle East. Communal roosts of Short-toed Eagles have not been reported either in the African winter quarters or during migration. This is the first description of a communal roost of Short-toed Eagles, and suggests that communal roosting might occur even in comparatively solitary species.
Keywords: Águilas culebreras; Short-toed Eagle; Communal roost; Strait of Gibraltar